Gastroprotective Effect of Abelmoschus esculentus (Ex-Maradi Okra Fruit Variety) Against Ethanol-Induced Ulcers in Rats - Muhammad, I.; Matazu, K. I.; Kankia, I. H.; Nasir, A.; Yau’, S.; Shamsu, S.; Suleiman, Z. A.; Nasir, R.; Sani, A. S.; Lawal, R. G.; Rawayau, M. A.; Darma, I. S.; et al. (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt